2018
DOI: 10.1002/cssc.201802198
|View full text |Cite
|
Sign up to set email alerts
|

Three Generations of Cobalt Porphyrins as Catalysts in the Oxidation of Cycloalkanes

Abstract: Three generations of cobalt porphyrins were synthesized, physicochemically characterized by FTIR and UV/Vis spectroscopy as well as cyclic voltammetry and applied as catalysts in the oxidation of cycloalkanes with atmospheric molecular oxygen under mild conditions. All examined catalysts were active in the tested reaction, and their catalytic activity varied with the nature and number of substituents on the porphyrin ring. Introduction of electron‐withdrawing or electron‐donating substituents at the porphyrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…These issues will be the subject of a separate publication (in preparation), where cobalt complexes will be compared with other transition metal complexes. From the literature and our unpublished calculations, it follows that some ligands, especially those containing nitrogen moieties, favor the exchange with the O 2 molecule [49,50]. Our unpublished calculations of HPA complexes show that, e.g., water and acetonitrile are not exchanged with the O 2 molecule, but are exchanged with OOH or H 2 O 2 .…”
Section: Introductionmentioning
confidence: 74%
“…These issues will be the subject of a separate publication (in preparation), where cobalt complexes will be compared with other transition metal complexes. From the literature and our unpublished calculations, it follows that some ligands, especially those containing nitrogen moieties, favor the exchange with the O 2 molecule [49,50]. Our unpublished calculations of HPA complexes show that, e.g., water and acetonitrile are not exchanged with the O 2 molecule, but are exchanged with OOH or H 2 O 2 .…”
Section: Introductionmentioning
confidence: 74%
“…It was suggested that the UV–vis spectrum is the fingerprint of the structure of TPPMnCl. The Soret band is formed by the strong electron transition in the TPPMnCl from the ground state to the second excited state, and the Q band is formed by the weak electron transition from the ground state to the first excited state . The positions of the Soret and Q bands of the TPPMnCl immobilized on the catalysts were collected and listed (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature, , the aldehyde could be catalytically oxidized by oxygen on transition metals, generating peroxyacid, which is known as one kind of ROS. , On the other hand, the metalloporphyrin can also be modified to accommodate a variety of catalytic systems. It is suggested that the electronic structure of the metal atom in metalloporphyrin plays an essential role in the catalytic oxygenation reaction . Moreover, the metalloporphyrin has received much attention in the ODS research.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt porphyrins provide a rich electrochemistry consisting of both metal- (Co(I)/Co(II)/Co(III) and porphyrin-centred redox processes. By variation of the substituents on the phenyl core of the porphyrin ligands, these processes can cover a huge range of potentials [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Moreover, there are one or two axial positions available for binding small molecules [ 10 , 11 , 12 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zn(II) [ 12 , 15 , 71 , 72 ] and Co(II) porphyrins [ 10 , 11 , 26 , 73 ] have been used as catalysts in the degradation of organic dyes with H 2 O 2 . In view of the first oxidation potential of Co(TPP) complexes lying in the range of 0.1 to 0.75 V vs. SCE [ 10 , 11 , 13 , 16 , 17 , 22 , 24 , 25 , 26 , 61 , 62 ], their high reactivity in radical-based organic transformations [ 14 , 58 , 59 , 60 ] is not unexpected and a very recent study on a (5,10,15,20-tetrakis(2,5-dimethoxyphenyl)porphyrinato)cobalt(II) has revealed some mechanistic details in such decomposition reactions using H 2 O 2 [ 73 ].…”
Section: Introductionmentioning
confidence: 99%